2013
DOI: 10.1155/2013/436913
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Electroacupuncture-Induced Analgesia on Neuropathic Pain in Animal Model

Abstract: Neuropathic pain remains as one of the most difficult clinical pain syndromes to treat. Electroacupuncture (EA), involving endogenous opioids and neurotransmitters in the central nervous system (CNS), is reported to be clinically efficacious in various fields of pain. Although multiple experimental articles were conducted to assess the effect of EA-induced analgesia, no review has been published to assess the efficacy and clarify the mechanism of EA on neuropathic pain. To this aim, this study was firstly desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 121 publications
1
36
0
1
Order By: Relevance
“…34,35) It has been reported that acupuncture or EA analgesia is centrally mediated by activation of the descending pain inhibitory system that finally involves spinal opioidergic, noradrenergic and cholinergic receptors. 13,27,36) Our previous studies indicate that each of these endogenous analgesic systems substantially contribute to the anti-allodynic effect of EA in peripheral nerve-injured rats. 20,37,38) Specifically for the cholinergic mechanism, spinal muscarinic receptors, but not nicotinic receptors, were involved in such EA effect.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…34,35) It has been reported that acupuncture or EA analgesia is centrally mediated by activation of the descending pain inhibitory system that finally involves spinal opioidergic, noradrenergic and cholinergic receptors. 13,27,36) Our previous studies indicate that each of these endogenous analgesic systems substantially contribute to the anti-allodynic effect of EA in peripheral nerve-injured rats. 20,37,38) Specifically for the cholinergic mechanism, spinal muscarinic receptors, but not nicotinic receptors, were involved in such EA effect.…”
Section: Discussionmentioning
confidence: 98%
“…EA-induced analgesia is mediated by the endogenous opioid and/or the non-opioid analgesic system, such as the central noradrenergic, cholinergic, serotonergic and γ-aminobutyrate (GABAergic) pain inhibitory pathways. 13) In contrast, the analgesic effects of BV injection are reported to be mainly mediated by the central noradrenergic system, but not by the endogenous opioids. 14,15) In a rat model of oxaliplatin-induced neuropathic pain, we recently demonstrated that EA significantly relieves acute cold allodynia via the release of the endogenous opioids, but not via the activation of the noradrenergic system.…”
mentioning
confidence: 99%
“…Acupuncture also has been reported to activate some brain structures such as the periaqueductal gray, nucleus raphe magnus, locus coeruleus, and arcuate nucleus that contribute to descending inhibitory modulation, as well as deactivate multiple limbic areas modulating pain emotion, such as insula and the anterior cingulate cortex. 8,9,20-22,30,42,55,68 …”
Section: Discussionmentioning
confidence: 99%
“…Based on a systematic review by Chen et al 22 acupuncture points most often used in dealing with diabetic neuropathy are ST36 Zusanli, GB34 Yanglingquan, SP6 Sanyinjiao, KI3 Taixi on the lower extremities, whereas in the upper limb are LI11 Quchi, LI4 Hegu, SJ5 Waiguan, and PC6 Neiguan. Kim et al 23 conducted another systematic review on several experimental studies to see the effect of electro-acupuncture on neuropathic pain. This study showed that stimulation of acupuncture points ST36 Zusanli and SP6 Sanyinjiao could activate μ and δ opioid, GABA-ergic, cholinergic, and 5-HT3 serotonergic receptors in the central nervous system, which not only played a role in various areas of pain, 23 but also in the cellular mechanisms of laser-puncture on wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 23 conducted another systematic review on several experimental studies to see the effect of electro-acupuncture on neuropathic pain. This study showed that stimulation of acupuncture points ST36 Zusanli and SP6 Sanyinjiao could activate μ and δ opioid, GABA-ergic, cholinergic, and 5-HT3 serotonergic receptors in the central nervous system, which not only played a role in various areas of pain, 23 but also in the cellular mechanisms of laser-puncture on wound healing. 4 In addition, the stimulation on ST36 Zusanli and SP6 Sanyinjiao acupuncture points may affect connective tissue through mechanical forces transferred to the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%